Genre Analysis of Daily COVID-19 Infographic Reports in the Arabian Gulf: The Case of the Kingdom of Bahrain - Mervat I. Albufalasa; Yasser A. Gomaa (Journal of English Language Teaching and Linguistics, 2022)
Infographics are visual data that are used in public service announcements to convey particular messages to a particular group of people. During the COVID-19 pandemic, the Ministry of Health (MOH) in the Kingdom of Bahrain relied heavily on the use of infographics to communicate different types of information to all its people. The study at hand aimed to analyze the Medical Announcement Infographics (MAIs) published by the Bahraini MOH during the pandemic. Two research questions were posited. The first one investigated the schematic moves in MAIs, and the second one researched the extent to which the Bahraini Medical Announcement infographics on COVID-19 Pandemic met the contextual variables of register. The study utilized Swales’ genre-analysis model and examined the contextual variables of the MIA register and the lexicogrammatical features highlighted in Systemic Functional Linguistics in relation to the Bahraini MOH’s MAIs. The study concluded that the register variables showed variation in the lexical, structural, and illocutionary force choice-making. In addition, MAIs included both obligatory and optional moves that impacted the behavioral attitudes of the people either positively or negatively.